A ferritin nanoparticle vaccine based on the hemagglutinin extracellular domain of swine influenza A (H1N1) virus elicits protective immune responses in mice and pigs - Tang, Pan; Cui, Enhui; Cheng, Jinghua; Li, Benqiang; Tao, Jie; Shi, Ying; Jiao, Jiajie; Du, Enqi; Wang, Jingyu; Liu, Huili (Frontiers in Immunology, 2024)
Swine influenza viruses (SIVs) pose significant economic losses to the pig industry and are a burden on global public health systems. The increasing complexity of the distribution and evolution of different serotypes of influenza strains in swine herds escalates the potential for the emergence of novel pandemic viruses, so it is essential to develop new vaccines based on swine influenza. Here, we constructed a self-assembling ferritin nanoparticle vaccine based on the hemagglutinin (HA) extracellular domain of swine influenza A (H1N1) virus using insect baculovirus expression vector system (IBEVS), and after a prime-boost two immunizations, the immunogenicities and protective efficacies of the HA-Ferritin nanoparticle vaccine against the swine influenza virus H1N1 strain in mice and piglets were evaluated. Our results demonstrated that HA-Ferritin nanoparticle vaccine induced broader and more efficient immunity than traditional swine influenza vaccines. Vaccination with the HA-Ferritin nanoparticle vaccine elicited robust hemagglutinin inhibition titers and antigenspecific IgG antibodies and increased cytokine levels in serum. MF59 adjuvant can significantly promote both the humoral and cellular immunity of HA-Ferritin nanoparticle vaccine. Furthermore, challenge tests showed that HA-Ferritin nanoparticle vaccine conferred full protection against lethal challenge with H1N1 virus and significantly decreased the severity of virus-associated lung lesions after challenge in both BALB/c mice and piglets. Taken together, these results indicate that the hemagglutinin extracellular-based ferritin nanoparticle vaccine may be a promising vaccine candidate against SIVs infection.